a Export Craft MSMEs' Performance and Financial Literacy: The Mediating Function of Financial Inclusion in Bangkalan, East Java - Ratnawati; MTN, Rokhman; Esy Suraeni, Yuniwati (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of financial literacy on MSME performance with financial inclusion as a mediating variable. The sample consists of 120 export craft MSME actors in Bangkalan, Madura. SmartPLS was employed as the analytical method. Results show that financial literacy does not directly affect performance but significantly influences financial inclusion. Financial inclusion improves MSME performance and mediates the relationship between literacy and performance. These findings imply the need for policies supporting financial literacy and inclusion to enhance the competitiveness and sustainability of MSMEs.